Medium range prediction of tropical cyclogenesis of intense vortices over Indian Seas by a Global Spectral Model - GUPTA, AKHILESH; RAMESH , K. J.; MOHANTY, U. C. (MAUSAM, 1998)
The performance of a Global Spectral Model (T-80) operational at the National Centre for Medium Range Weather Forecasting (NCMRWF), New Delhi in predicting the cyclogenesis of six tropical cyclones over Indian Seas formed during 1995-96 has been evaluated. It has been found that the model has the capability to predict cyclogenesis in wind field at least 72 hours in advance although the positions of predicted vortices are seen to be displaced from those of analysed ones in some cases. The quantitative estimates of the atmospheric conditions favourable for cyclogenesis also confirm the conclusions drawn from the qualitative analysis of cyclogenesis predictions of the model in terms of appearance of cyclonic circulation. It also follows from this analysis that the predicted circulations at the cyclogenesis stage are in general more intense and stronger as compared to the corresponding analysis in terms of wind and mass fields. On examining the model systematic errors of prediction it is found that the model has a clear bias for predicting more intense vortex during genesis and weakening stages. On the order hand it predicts relatively less intense vortex during intensification process.